PERBANDINGAN KOMPOSISI ASAM LEMAK KELAPA SAWIT (Elaeis guineensis Jacq.) HASIL TRANSFORMASI GENETIK - Faturrahman Faturrahman (Jurnal Agroteknologi, 2013)
The objective of this research is to be able to observe the results of the integration as well as the expression of the desaturase gene in the antisense conformation. The selection of an appropriate tissue culture media is required for a faster growth, development and regeneration of the explant. PCR analysis shows that the putative transgenes were successfully inserted into the target tissue. They were then analysed via gas chromatography to detect its effect on the fatty acid profile. As a result, it was discovered that the three plants contained a higher level of saturated fatty acids (C:12 – C:18), as well as a reduced level of unsaturated fatty acids (C18:1 – C18:3). This probably shows that the stearoyl-ACP desaturase gene might be able to block or reduce the levels of unsaturated fatty acid while increasing the levels of saturated fatty acid. As this are preliminary results further work needs to be carried out to verify this observation.